Proceedings of the International Conference on Web Search and Web Data Mining - WSDM '08 2008
DOI: 10.1145/1341531.1341549
|View full text |Cite
|
Sign up to set email alerts
|

Preferential behavior in online groups

Abstract: Online communities in the form of message boards, listservs, and newsgroups continue to represent a considerable amount of the social activity on the Internet. Every year thousands of groups flourish while others decline into relative obscurity; likewise, millions of members join a new community every year, some of whom will come to manage or moderate the conversation while others simply sit by the sidelines and observe. These processes of group formation, growth, and dissolution are central in social science,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 34 publications
1
50
2
Order By: Relevance
“…Romero and Kleinberg [2010] study the problem of the triadic closure process and develop a methodology based on preferential attachment, for studying the directed triadic closure process. Backstrom et al [2008] propose a partitioning on the data that selects for active communities of engaged individuals.…”
Section: Triadic Closure Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Romero and Kleinberg [2010] study the problem of the triadic closure process and develop a methodology based on preferential attachment, for studying the directed triadic closure process. Backstrom et al [2008] propose a partitioning on the data that selects for active communities of engaged individuals.…”
Section: Triadic Closure Formationmentioning
confidence: 99%
“…Previous research on social relationships can be classified into three categories: link prediction [Liben-Nowell and Kleinberg 2007;Romero and Kleinberg 2010;Leskovec et al 2010;Backstrom and Leskovec 2011], relationship type inferring [Eagle et al 2009;Crandall et al 2010;Wang et al 2010;Tang et al 2011], and social behavior prediction [Backstrom et al 2008;Tan et al 2010;Yang et al 2010]. Backstrom and Leskovec [2011] propose an approach called supervised random walk to predict and recommend links in social networks.…”
Section: Introductionmentioning
confidence: 99%
“…Straightforward measures such as number and frequency of posting are often used as an index of community health. For example, it has been shown that the activity of a group can be maintained in high levels by long term members, who help keep the group together [1,10]. On the other hand, it has been found that having lurkers in a community does not necessarily have a negative influence [12].…”
Section: Related Workmentioning
confidence: 99%
“…However, the members in topical groups may not know each other in the real world. They gather in the same group as they have some common interest [17].In the QQ groups, a user's experience in group may be influenced by others' behavioral in the group [18]. For example, if someone sends a message in a group but no one replies him, he will leave this group probably.…”
mentioning
confidence: 99%
“…However, the members in topical groups may not know each other in the real world. They gather in the same group as they have some common interest [17].…”
mentioning
confidence: 99%